Development of public research and development organizations: international experience and lessons for Vietnam - Nguyen Thi Minh Hanh; Nguyen, Thi Minh Nga; Nguyen, Manh Kiem (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
In the world, the establishment of state-owned research and development organizations, also known as public research organizations, is a fairly common form of S&T activities in the recent years 1960, 1970 of the last century. Undeniably, in certain historical periods, public research institutions have made important and decisive contributions to the outstanding socio-economic development, as well as science and technology of many countries. In the following article, the author reviews the background of the birth, roles and contributions of some typical public research institutions in history; The trend of reforming public research institutions in the world, thereby proposing some lessons for Vietnam in continuing to renovate the system of public research institutions. The article also contributes to the implementation of Decision No. 279/QD-TTg dated February 26, 2021 of the Prime Minister approving the planning of the network of public S&T organizations for the period of 2021-2030, with a vision to 2050. Code: 22032101